Zakat Distribution Consept at LAZISMU Pamekasan and Its Relevance to Umar Bin Khattabs Zakat Distibution - Nurul Fitriyah; Rudy Haryanto; Zainal Abidin (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2023)
This research aims to determine the concept of zakat distribution in LAZISMU Pamekasan and its relevance to umar bin khattabs zakat distibution. This research uses a qualitative research method, which is explanatory qualitative research with a field research type of research. Data collection was carried out using non participan observation methods, semi structured interviews, and documentation methods. The results of the research show that, in terms of regulation, LAZISMU Pamekasans zakat distribution pattern follows central regulations origininating from Law Number 23 of 2011 concerning zakat in Indonesia. Some of Umar bin Khattabs zakat policies, especially in zakat distribution, are relevant to the zakat distribution pattern at LAZISMU Pamekasan because they are both centered on government regulations. Umar bin Khattab has full authority over the zakat policy for the reasons of avoiding corrupt practices and unfair and equitable distribution.